Effects of Epileptic Seizures and Carbamazepine on Brainstem Auditory Evoked Potentials - Koçak, Nuri; Aygül, Recep; Deniz, Orhan; Orhan, Asuman (Fırat University, 2005)
Objectives: In the prolonged use of antiepileptic drugs (AEDs), the functions of central nervous system have been influenced without clinical neurotoxicity indications. In this study, the effects of epilepsy and carbamazepine (CBZ) use in epilepsy on the brainstem auditory pathway functions were investigated by brainstem auditory evoked potentials (BAEP) which is a useful and noninvasive test. Materials and Methods: This study was carried out in 19 newly diagnosed epileptic patients and 26 epileptic patients receiving CBZ more than 6 months (mean age: 27.45±12.23 years). Thirty-two similarly age-matched healthy subjects were taken as the control group. I., III. and V. wave peak latencies, and I-III, I-V, and III-V inter-peak latencies (IPLs) were determined in all subjects. The relationship of BAEP with blood drug level and therapy period was investigated. Results: Compared to the control group, wave I and III mean latencies were found significantly prolonged in CBZ using group (p < 0.05), but no significant difference was found in terms of I-V IPLs (p > 0.05). Additionally, there was a significant positive correlation between serum CBZ level and I-V IPLs (r value: 0.497, p < 0.05). In the drug-naÃ¯ve epileptic group, wave III and V mean latencies were found increased but did not reach a statistical significance. Conclusion: The findings show that CBZ can suppress brainstem auditory pathway at different levels, and may also influence the time of central conduction depending on serum drug levels. Additionally, it was found that mild involvement in brainstem functions might be observed in drug-naÃ¯ve epileptic patients. ©2005, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Antiepileptik ilaçların (AEİ) uzun süre kullanımında klinik nörotoksisite belirtileri olmadan da santral sinir sistemi fonksiyonları etkilenmektedir. Bu çalışmada, epilepsi ve karbamazepin (CBZ) kullanımının beyin sapı fonksiyonları üzerine etkilerinin, yararlı ve noninvaziv bir test olan işitsel uyarılmış potansiyellerle (BAEP) değerlendirilmesi planlandı. Gereç ve Yöntem: Çalışmaya epilepsi tanısı yeni konmuş AEİ kullanmayan ve 6 ay ve üzerinde CBZ monoterapisi alan 45 epileptik olgu (yaş ort.27.45±12.23 yıl) ve yaş olarak benzer 32 sağlıklı kontrol alındı. Bütün subjelerin I., III., ve V. dalga latansları ile I-III, III-V, I-V interpik latansları (IPL) BAEP kayıtları ile belirlendi. İlaç kullanma süresi ve ilaç kan düzeyi ile BAEP anormalliklerinin korelasyonuna bakıldı. Bulgular: Bulgular, CBZ'nin beyin sapı işitsel yollarını farklı seviyelerde suprese edebileceğini ve kan düzeyine bağlı olarak santral iletim zamanını da etkileyebileceğini göstermektedir. İlaç kullanmayan epileptiklerde de beyin sapı yapılarının ılımlı etkilenebileceği düşünülebilir. Sonuç: CBZ kullanan 26 olgunun BAEP I. dalga ve III. dalga ortalama latans değerleri kontrol grubuna göre anlamlı uzamıştı (p < 0.05). I-V IPL arasında farklılık belirlenmedi (p > 0.05). I-V IPL'lar ve CBZ serum düzeyi arasında pozitif korelasyon vardı (r value: 0.497, p < 0.05. AEİ kullanmayan 19 olgunun III. ve V. dalgalarının ortalama latansları kontrollere göre daha uzun olmasına rağmen farklılık anlamlı düzeye ulaşmıyordu. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Epileptik Nöbetler ve Karbamazepinin Beyin Sapı İşitsel Uyarılmış Potansiyelleri Üzerine Etkisi